Original paperProtective effect on visual functions of long-term use of trimetazidine in treatment of primary open angle glaucoma and degenerative myopia - Nowak, Michał S.; Wybór, Katarzyna; Goś, Roman; Zeman-Miecznik, Alicja; Waszczykowska, Arleta; Pastuszka, Mirosław; Kłysik, Anna; Gajdowska, Agnieszka (Archives of Medical Science, 2007)
Introduction: The purpose of the study was to evaluate selected visual parameters in the group of patients undergoing long-term treatment with trimetazidine as an adjuvant therapy for primary open angle glaucoma and degenerative myopia. Material and methods: Thirty patients, including 20 patients with advanced primary open angle glaucoma (40 eyes) and 10 patients with severe degenerative myopia (20 eyes), were treated with trimetazidine 20 mg twice a day. We excluded from the study patients with: systemic hypertension and/or diabetes, cataract, history of chronic and recurrent severe inflammatory eye disease and smokers. Patients with primary open angle glaucoma were taking various ocular hypotensive drops topically. Ophthalmic examination has been performed before administration of trimetazidine and then every month. Visual acuity, contrast sensitivity test (Pelli-Robson test), glare test, color vision (Farnsworth-Munsell test) and visual field were recorded. Follow-up period was 6 months. For statistical analysis paired Student’s t- test (p<0.05) was used. Results: The contrast sensitivity and visual acuity improved in all patients and the results were statistically significant. Glare tests, colour vision and visual fields did not reveal any statistically significant changes. Conclusions: The results of the study demonstrate that long term use of trimetazidine improved contrast sensitivity and visual acuity. The drug was well tolerated and might be considered as the adjunctive therapy in patients with primary open angle glaucoma and degenerative myopia.